Techno-Economic Analysis of Linear Low-Density Polyethylene Plant Using Sclairtech Process Optimized by Heat Integration - Gandi Prasetyo; Hari Rionaldo; Dian Dharmayanti; Novia Syafril (Applied Engineering, Innovation, and Technology, 2025)
Polyethylene (C2H4)n is a crucial industrial material in the plastics industry, produced via ethylene polymerization. The rising demand for Linear Low-Density Polyethylene (LLDPE) and advancements in process technology make the establishment of an LLDPE plant in Indonesia feasible. This paper aims to evaluate the feasibility of such a plant using the Sclairtech process. The heat exchanger network is designed using the Temperature Interval and Composite Curve Methods. The economic feasibility analysis, performed using the study estimate method with bare module costs, shows significant utility savings through heat integration, reducing utility costs from USD 3,933 to USD 1,510 per hour. The plant's Payback Period (PBP) is 3.21 years, with a net present value (NPV) of USD 250.48 million, an internal rate of return (IRR) of 16%, and a breakeven point of 31.04%. Sensitivity analysis indicates the plant remains profitable despite a 65.22% increase in raw material costs and a 100% reduction in product prices. Based on the Heat Integration design and economic analysis, the LLDPE plant using the Sclairtech process is deemed economically viable.